Several household chemical exposures are associated with pediatric‐onset multiple sclerosis. Issue 12 (9th October 2018) - Mar, Soe; Liang, Shannon; Waltz, Michael; Casper, T. Charles; Goyal, Manu; Greenberg, Benjamin; Weinstock‐Guttman, Bianca; Rodriguez, Moses; Aaen, Gregory; Belman, Anita; Barcellos, Lisa F.; Rose, John; et al.
Abstract: Background: There is limited information about the potential associations of multiple sclerosis (MS) and commonly used household chemicals. Methods: We performed a case‐control study of exposures to common household chemicals during childhood in children with MS and healthy pediatric controls. Exposures to household products were collected from a comprehensive questionnaire (http://www.usnpmsc.org/Documents/EnvironmentalAssessment.pdf ) completed by parents at the time of enrollment in the study. Cases included children diagnosed with MS or clinically isolated syndrome with at least two silent T2 bright lesions on MRI, recruited within 4 years of disease onset from 16 pediatric MS clinics in the USA. Multivariate analyses using logistic regression were adjusted for possible confounders including age, sex, race, ethnicity, mother's highest level of education, and urban versus rural living. Results: Questionnaire responses to household chemicals were available for 312 eligible cases (median age 15.7 years, 63% girls) and 490 healthy controls (median age 15.0, 57% girls). Exposure to rodenticides (odds ratio [OR] 2.10, 95% confidence interval [CI] 1.35–3.26, P ≤ 0.001), weed control agents (OR 1.99, 95% CI 1.36–2.92, P ≤ 0.001) and products for plant/tree disease control (OR 2.72, 95% CI 1.54–4.82, P ≤ 0.001) anytime during childhood were associated with an increased risk for pediatric‐onset MS in adjusted and multiple comparisons analyses. Conclusions: Our findings suggest that exposure to specific household chemicals during early childhood is associated with the risk of developing pediatric‐onset MS. Future studies are needed to elucidate a causal relationship and the exact agents involved.